2022
DOI: 10.1109/jsyst.2021.3107331
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Unit Protection for Lines Connecting Large Solar Plants Using Incremental Current Ratio

Abstract: Control schemes in a solar plant complying with different grid codes modulate the output voltage and current significantly during fault. In this paper, the issue with conventional current differential approaches for the line connecting large solar plant is analyzed and a new protection technique using both end incremental current phasors is proposed. The proposed method uses two criteria to identify the internal faults in such connectivity. The first criterion is based on the ratio of both end incremental phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The Thevenin's equivalent of the grid is represented using a voltage source (E 1Gpre ) with an internal impedance (Z 1G ) in series. The grid following converter connecting solar plant is represented with a dependent current source (I 1Spre ) in parallel with a high impedance (Z 1P V ) [21]. The solar plant is connected to bus M with the positive sequence transformer impedance Z 1tr .…”
Section: System Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Thevenin's equivalent of the grid is represented using a voltage source (E 1Gpre ) with an internal impedance (Z 1G ) in series. The grid following converter connecting solar plant is represented with a dependent current source (I 1Spre ) in parallel with a high impedance (Z 1P V ) [21]. The solar plant is connected to bus M with the positive sequence transformer impedance Z 1tr .…”
Section: System Descriptionmentioning
confidence: 99%
“…X 1L , X eq F and R eq F in (21) being always positive, a relation is derived in (22), which is valid for all symmetrical and asymmetrical faults.…”
Section: A Identification Of Zone-1 Fault In Parallel Linesmentioning
confidence: 99%
“…Investigations of LCD protection in the presence of CIS have been presented in [8][9][10][11]. In [8,9], characteristics of the converter fault current using a dual sequence current controller with different control objectives are analysed, which demonstrate that fault conditions and control objectives could both influence the fault current angles.…”
Section: Introductionmentioning
confidence: 99%
“…[10] and [11] present mathematical expressions for representing fault contributions from the CIS and the grid into an LCD operating characteristic, under the assumption of a relatively strong grid-side fault contribution. In [10], the mathematical expression for the CIS current references under different control strategies are derived, while in [11] the controlled nature of CIS fault waveforms are represented as a voltage dependent current source in parallel with a variable impedance. It was demonstrated that the line length, CIS capacity, fault location and fault severity could all influence the performance of the LCD protection.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous control options, embedded in the converters meeting different requirements for reliable power system operation, compel such sources to respond differently compared to conventional synchronous generators during fault [2]. The growing rate of relay maloperation following renewable integration impels to revisit every aspect associated with protection decisions [3][4][5][6]. Faulted phase selection is such a task, which is essential in deriving protection decisions like auto-reclosing, distance relaying, single-pole-tripping, etc.…”
Section: Introductionmentioning
confidence: 99%